A Multifunctional Well-Placement in an Oil Rim Reservoir (British Journal of Multidisciplinary and Advanced Studies, 2025)
Enhancing hydrocarbon production and optimizing recovery at the lowest possible cost are the objectives of an oil field development research. Coning issues, gas smeared, and oil lost into the gas cap are always linked to optimizing oil production from oil rim reservoirs with an underlying aquifer and an overlaying gas cap. These issues will lower the oil recovery factor. Oil rim reserves are viewed as marginal by the majority of oil firms. A model with a horizontal and multilateral well in an oil rim reservoir is simulated using the Schlumberger Eclipse 100 Black oil simulator, with the horizontal well serving as the base-case. Sensitivity analysis, cost evaluation of the advantages of the multilateral well over the horizontal well, and the impact of standoff from such reservoirs were also investigated. The analysis of the simulation results, cost analysis, and sensitivity analysis revealed that the horizontal well produced 132,287 STB, a higher field oil production rate, and a good amount of profit than the multilateral well, which presented an increased oil production total of 134,135 STB. With 132,287 STB, the horizontal well's standoff resulted in the highest oil recovery production because to its tiny size. However, when the standoff was severe and the laterals were widely spaced, more oil—134,135 STB—was collected from the multilateral well. According to the aforementioned findings, multilateral wells can be utilized in an oil rim reservoir to improve oil recovery as opposed to traditional techniques, which do not yield the best output and render the oil rim reservoir marginal.